2014
DOI: 10.1080/17470218.2013.846392
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Spell from Reading: General Knowledge about Spelling Patterns Influences Memory for Specific Words

Abstract: Adults often learn to spell words during the course of reading for meaning, without intending to do so. We used an incidental learning task in order to study this process. Spellings that contained double n, r and t which are common doublets in French, were learned more readily by French university students than spellings that contained less common but still legal doublets. When recalling or recognizing the latter, the students sometimes made transposition errors, doubling a consonant that often doubles in Fren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 40 publications
3
27
0
2
Order By: Relevance
“…In Experiment 1, as in some previous studies (Pacton et al, 2014;2013), participants read nonwords in texts without instruction to learn their spellings. In Experiment 2, we asked what happens when participants are explicitly asked to learn the items' spellings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Experiment 1, as in some previous studies (Pacton et al, 2014;2013), participants read nonwords in texts without instruction to learn their spellings. In Experiment 2, we asked what happens when participants are explicitly asked to learn the items' spellings.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have tested the idea that people's knowledge of graphotactic regularities influences their spelling by examining how they learn and remember novel spellings that they read in texts (Pacton, Borchardt, Treiman, Lété, & Fayol, 2014;Pacton, Sobaco, Fayol, & Treiman, 2013). Such tasks are well suited to investigate the learning of spelling and vocabulary, and they allow strict control over how often participants see each item (Burt & Fury, 2000;Brusnighan & Folk, 2012;Nation, Angell, & Castles, 2007;Share, 2004).…”
mentioning
confidence: 99%
“…In doing so, we demonstrated that Silex could be used to investigate how statistical learning (e.g., Negro, Bonnotte, & Lété, 2014) and grain-size theory (e.g., Ziegler & Goswami, 2005) apply to spelling (see also Treiman & Kessler, 2014). That is, Silex can be used to explore the effects of letter frequency (e.g., Pacton, Borchardt, Treiman, Lété, & Fayol, 2014) and preceding orthographic context (e.g., Pacton, Fayol, & Perruchet, 2005;Treiman, Kessler, & Bick, 2002) because it provides unconditional-and conditionalconsistency indices for silent-letter endings. In sum, the richness of the information provided in Silex is such that it should enable researchers to test a number of specific hypotheses about spelling acquisition and skilled performance.…”
Section: Introductionmentioning
confidence: 94%
“…hart instead of heart). Additional evidence for the influence of sub-lexical orthographic regularities on the memorisation of novel orthographic representations was recently uncovered by Pacton and colleagues by using an incidental learning paradigm (Pacton, Borchard, Treiman, Lété, & Fayol, 2013; see also Sobaco, Treiman, Peereman, Borchardt, & Pacton, 2015). Adult readers had to read a text that contained a target nonword whose spelling could be more or less frequent according to French orthography.…”
Section: Sub-components Of Orthographic Processing Skills and Their Rmentioning
confidence: 99%